Developing Web-Assisted Interactive Media to Improve Mathematical Creative-Thinking Ability - Rachmawati, Andini Dwi; Baiduri, Baiduri; Effendi, Mohammad Mahfud (Al-Jabar: Jurnal Pendidikan Matematika, 2020)
Millennials currently prefer web-assisted interactive media as a learning resource rather than reading books. To understand the contents of the book, students need high literacy skills. Unlike the web-assisted interactive media, the explanations are accompanied by pictures and simulations that can help students to understand the learning material. The developed web-assisted interactive learning media had been adjusted to the 2013 curriculum. This research aimed to develop a valid, effective, and practical interactive web-assisted learning media. The research development model used was the 4D model which consisted of Define, Design, Development, and Dissemination stages. The instrument used in this study was a validation sheet, a questionnaire to measure the practicality, and a creative-thinking test to measure the effectiveness. The results of validation showed that the developed learning media obtained an average score of 86.17% and had met the validity criteria with excellent quality. The questionnaire obtained a score of 88.39% which indicated that the developed learning media was effective. The developed web-assisted interactive learning media met the effectiveness criteria with the obtained average score of 80% based on four indicators, namely fluency, flexibility, authenticity, and detail. It can be concluded that the web-assisted interactive learning media is suitable to be used as a learning resource.